DISKRIMINASI PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG ORGANISASI MASYARAKAT NOMOR 02 TAHUN 2017 (Studi Kasus Pembubaran Organisasi Masyarakat Islam Hizbut Tahrir Indonesia) - Sattari Nur; Faradilla Fadlia; Novita Sari (Journal of Political Sphere, 2021)
ABSTRACTMass Organizations (Ormas) is a media or forum formed by a group of people based on the same ideology and desired goals that they want to achieve. The establishment of Ormas is regulated in Law No. 17 of 2013 concerning community organizations. Hizbut Tahrir Indonesia (HTI) is one of the mass organizations established in Indonesia based on Islamic ideology. Although the Indonesian government has given the freedom to develop mass organizations and received legal entities, the government also stipulates a binding regulation that can cause discrimination through a legal entity. This regulation is regulated in Government Regulation in Lieu of Law No. 02 of 2017. By means of this regulation, the government officially banned HTI as a mass organization in Indonesia. The aim of this study was to examine the implementation of the regulation or law that discriminates against an organization established by a group of people with Islamic ideology, such as HTI. The theories used in this study include social movement theory, discrimination theory, and the concept of the rule of law. The method used in this study was a descriptive qualitative method. This study revealed that there was institutional discrimination or indirect discrimination as a result of the stipulation of a political policy. From a legal perspective, the Government Regulation in Lieu of Lawis a legitimate law. However, it might have caused problems in its implementation because several articles have been deleted without involving the judiciary board in the process. It can be concluded that the Government Regulation in Lieu of Law concerning Ormas does not legally bring about discrimination. However, it was its implementation that indicates that there was discrimination against a particular organization. The disbandment of HTI should have been carried out per the applicablelawto ensure harmony from one regulation or law to another. These will prevent discrimination against HTI when the government revoked its legal status. Keywords: Government Regulation in Lieu of Law of Ormas, HTI, Discrimination